The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.14238/pi59.1.2019.38-43
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and outcomes of pediatric diphtheria

Abstract: Background Although vaccination programs have succeeded in reducing the incidence of diphtheria, it remains a health problem in Asia, including Indonesia. Objective To investigate the clinical spectrum and outcomes of pediatric diphtheria in Wahidin Sudirohusodo Hospital. Methods This study was a retrospective review of childhood diphtheria medical records from January 2011 to December 2017 in Wahidin Sudirohusodo Hospital, Makassar, South Sulawesi. Recorded data consisted of age, gender, nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
(21 reference statements)
4
5
0
Order By: Relevance
“…We observed that children who had completed their vaccination were more prone to get infected than children who were unvaccinated or partially vaccinated. In agreement to our results, (Alfiansyah, 2015) and (Nawing et al, 2019) reported children with completed vaccination had the highest incident of diphtheriae. These studies also observed more children with completed vaccination experienced the disease (Arifin & Prasasti, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that children who had completed their vaccination were more prone to get infected than children who were unvaccinated or partially vaccinated. In agreement to our results, (Alfiansyah, 2015) and (Nawing et al, 2019) reported children with completed vaccination had the highest incident of diphtheriae. These studies also observed more children with completed vaccination experienced the disease (Arifin & Prasasti, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Similar results stated myocarditis was the most common complications done by (Arya et al, 2022;Dyah Nugroho et al, 2019;Liansyah et al, 2020;Nawing et al, 2019). Sign of myocarditis wasn't met clinically.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A study in India revealed that most diphtheria cases were non-vaccination (79%) or incomplete vaccination (18%), with CFR in 48% and tracheostomy in approximately 50% of the cases (22). Nawing et al also described fatal cases that had not received a vaccination or had received it partially (23). Furthermore, three-quarters of the cases had unidentified contact.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive population in an area may cause a slum environment that may become breeding site for Corynebacterium diphtheria. Others include low vaccination coverage, crowding, migration or population movement, environmental factors, nutritional status, parental behavior, and personal hygiene of children (15). Research conducted in Yemen, diphtheria cases were mostly found in areas with massive population displacement, non-functioning services, lack of food, poor clean water, and poor sanitation (16).…”
Section: Distribution Of Diphtheria Incidence and Community Lead Tota...mentioning
confidence: 99%